Hubungan Stres Akademik dengan Kecenderungan Depresi Mahasiswa Ilmu Keperawatan Universitas Gadjah Mada pada Masa Transisi Pandemi COVID-19 - Afna Hanung Azizah; Sri Warsini; Kurnia Putri Yuliandari (PSIK FKKMK UGM, 2023)
Background: College students as a group who are experiencing the transition from adolescence to early adulthood, are at risk of experiencing stress problems, especially academic-related stress. This condition has been exacerbated by the COVID-19 pandemic which has changed the education system in Indonesia. Experiencing high academic stress without any effort to overcome it, can potentially lead to depressive disorders. Research on the correlation between academic stress and depression tendencies among nursing students during the transition of COVID-19 pandemic has never been conducted.Objective: To determines the correlation between academic stress and depression on nursing students in School of Nursing, Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada in post pandemic COVID-19.Method: This study was an analytic observational study with a cross-sectional design. The research population was nursing students in School of Nursing, FK-KMK UGM. Data was collected in December 2022. The samples were 185 respondents obtained through stratified random sampling. This study used Academic Stress Scale questionnaire and The Patient Health Questionnaire 9 (PHQ-9) questionnaire. Data were analyzed using Spearman’s correlative test.Results: All nursing students in UGM experienced moderate academic stress in post pandemic COVID-19 and the majority of respondents (43,8%) showed a mild tendency to depression. The correlation test between academic stress and depression analysis showed a correlation coefficient (r) of 0,597 with a significant value of 0,000. Conclusion: There is strong significant correlation with a positive direction between academic stress and depression in nursing students during post pandemic COVID-19.ABSTRAKLatar belakang: Mahasiswa sebagai kelompok usia yang mengalami transisi dari masa remaja ke dewasa awal, berisiko mengalami masalah stres, terutama yang bersumber dari proses akademik. Kondisi ini diperparah dengan adanya pandemi COVID-19 yang mengubah sistem pendidikan di Indonesia. Tingginya kondisi stres akademik yang dialami dan tanpa upaya untuk mengatasinya, akan berpotensi menimbulkan gangguan depresi. Penelitian mengenai hubungan stres akademik dengan kecenderungan depresi pada mahasiswa ilmu keperawatan pada masa transisi pandemi COVID-19 belum pernah dilakukan sebelumnya. Tujuan: Mengetahui hubungan antara stres akademik dengan kecenderungan depresi pada mahasiswa ilmu keperawatan UGM pada masa transisi pandemi COVID-19.Metode: Penelitian ini merupakan penelitian analitik observasional dengan rancangan cross sectional. Populasi penelitian yaitu mahasiswa Ilmu Keperawatan UGM angkatan 2019, 2020, dan 2021. Jumlah sampel sebanyak 185 mahasiswa yang didapatkan melalui stratified random sampling. Kuesioner yang digunakan adalah Skala Stres Akademik dan The Patient Health Questionnaire 9 (PHQ-9). Analisis data menggunakan uji korelatif Spearman. Hasil: Pada masa transisi pandemi COVID-19, semua responden mengalami stres akademik pada tingkat sedang dan mayoritas responden (43,8%) menunjukkan kecenderungan depresi pada tingkat ringan. Hasil analisis uji korelasi antara stres akademik dengan kecenderungan depresi menunjukkan koefisien korelasi (r) 0,597 dengan nilai signifikansi 0,000.Kesimpulan: Terdapat hubungan kuat dengan arah positif antara stres akademik dan kecenderungan depresi pada mahasiswa ilmu keperawatan transisi pandemi COVID-19.